Beyond Vows: Unraveling Sundanese Customary Marriages by The Parental/Bilateral Kinship System - Karwiyah, Karwiyah; Nugroho, Bambang Daru; Kusmayanti, Hazar (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
This research investigates the intricate relationship between customary marriage laws and the unique kinship systems prevalent among indigenous communities, with a focus on the Sundanese people in West Java, particularly the Karawang Regency. In the captivating landscapes of West Java, Sundanese societies adhere to a parental/bilateral kinship structure, where familial ties intricately shape their customs.This paper explores the nuanced interplay between legal regulations and cultural practices in Sundanese customary marriages. Beyond procedural adherence, these unions are deeply rooted in both legal frameworks and community traditions. The research adopts a juridical normative approach, utilizing descriptive-analytical methods. Primary, secondary, and tertiary legal materials undergo scrutiny through extensive literature research, complemented by on-the-ground observations. The study aims to provide a comprehensive overview of the legal dynamics and sanctions associated with customary marriages within the Sundanese parental/bilateral kinship system. By intertwining legal insights and cultural nuances, this research contributes to a deeper understanding of how the Sundanese community navigates the delicate balance between legal requirements and cherished traditions in the realm of matrimony.